Nuclear Receptors as Targets for Drug Development: Molecular Mechanisms for Regulation of Obesity and Insulin Resistance by Peroxisome Proliferator-Activated Receptor , CREB-Binding Protein, and Adiponectin - Atsushi Tsuchida; Toshimasa Yamauchi; Takashi Kadowaki (Elsevier, 2005)
Obesity is defined as increased mass of adipose tissue, conferring a higher risk of cardiovascular and metabolic disorders such as diabetes, hyperlipidemia, and coronary heart disease. To investigate the role of transcriptional factors, which are involved in adipocytes differentiation and adiposity, we have generated peroxisome proliferator-activated receptor (PPAR) γ or CREB-binding protein (CBP)-deficient mice by gene targeting. Heterozygous PPARγ-deficient mice were protected from the development of insulin resistance due to adipocyte hypertrophy under a high-fat diet. Heterozygous CBP-deficient mice showed increased insulin sensitivity and were completely protected from body weight gain induced by a high-fat diet. PPARγ or CBP deficiency results in increased effects of hormones such as adiponectin and leptin. Adiponectin was decreased in obesity and lipoatrophy, and replenishment of adiponectin ameliorated insulin resistance. Moreover, adiponectin-deficient mice showed insulin resistance and atherogenic phenotype. Finally, cDNA encoding adiponectin receptors (AdipoR1/R2) have been identified by expression cloning. The expression of AdipoR1/R2 appears to be inversely regulated by insulin in physiological and pathophysiological states such as fasting/refeeding, insulin deficiency, and hyperinsulinemia models, and it is correlated with adiponectin sensitivity. These results facilitate the understanding of molecular mechanisms of adiponectin actions and obesity-linked diseases such as diabetes and atherosclerosis and propose the molecular targets for anti-diabetic and anti-atherogenic drugs. Keywords:: peroxisome proliferator-activated receptor (PPAR) γ, CREB-binding protein (CBP), adiponectin, adiponectin receptor, insulin resistance